A study on common stressor among undergraduates in UiTM Kedah / Nurul Syamimi Zainal ... [et al.] - Zainal, Nurul Syamimi; Azmi, Muhamad Hafez Irfan; Jaafar, Muhammad Khaleed Shah (2012)
College students are synonymous with the stage of adolescent - occurs between childhood and adulthood. This is where young people experience rapid growth of their body and mentality to full maturity. Most memories have been undergone at this stage of transition - as the best time in life (good stress). However, these critical years of adjustment can also be undermined by depression and suicide (bad stress). These phenomenon may lead to good stress and bad stress - depending on how ones' reaction upon the stressor. Basically, the purpose of this article research was to identify what is the common stressor which constitute to the level of stress among undergraduates in UiTM Kedah. This article research was done to answer these research questions; what are the most stressor that constitute to the level of stress among undergraduates and what are the common stressor among undergraduates in UiTM Kedah. Therefore, the objectives of this research are to find out the stressor that constitute to the level of stress among undergraduates and the common stressor among undergraduates in UiTM Kedah. A questionnaire was designed to be distributed randomly to 50 undergraduates of UiTM Kedah. The significance of this article research was essential to identify the stressor which affects one's future performances especially in the workplace later. The research design for this study was a cross-sectional survey where the data will be gathered just once which over a period of a week in order to answer a research questions. Therefore, for this study, researchers used one time collection over a period of three (3) days time for the questionnaire to be distributed to undergraduates in UiTM Kedah. Data for this study will be collected through survey using questionnaire. The questionnaire for this study will consists of three (3) sections. In Section A, it will comprise a set of questions about the demographic of the respondents that consists of gender, age, CGPA, semester and course. The purpose of this Section is to know about the background of the respondents chosen. While for Independent Variables, Section B, it consists of possible stressor among undergraduates. The purpose of this Section is to know whether there is a relationship between backgrounds of the undergraduates with the students' factor of stress.